Ethical Issues in Global Pandemic Covid-19: Attitudes and Perceptions of the People of Bandung City Toward Contact Tracing and the Confidentiality Issues it Can Raise - Hashibah, Hasna; Mayasari, Wulan; Syukriani, Yoni Fuadah (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The COVID-19 pandemic has created an innovative space for technology to become a solution, which, if implemented effectively, can help reduce the negative impact of the pandemic on society. For example, contact tracing, which if done manually, requires more resources and takes a lot of time, even though the spread of COVID-19 is happening very quickly, so a faster task force response is also needed. This research aims to determine public perceptions of confidentiality issues that may arise from implementing COVID-19 contact tracing, as well as public attitudes towards implementing COVID-19 contact tracing. This research will use a quantitative study method using a cross-sectional method. The researchers used a phenomenological theoretical approach to find out how people view contact tracing. The results of this research show that the majority of people in Bandung City who were respondents to this research have a positive attitude towards contact tracing and support the implementation of contact tracing. Most of the people in Bandung City who were respondents to this research had a good perception of contact tracing and felt that their privacy would not be disturbed by contact tracing. So the government needs to ensure that the public can easily access the contact tracing method used. Health officials need to explain contact tracing in a way that is easy for the public to understand so that the public understands the purpose of implementing contact tracing. And the public should also seek the latest information about health and obey the recommendations of the government and health officials.